The Benefits of Informed Non-Dissent when Families have Difficulty Making a Decision - Nortje, Mila; Haque, Sajid; Nortje, Nico (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2022)
Being a surrogate decision-maker is challenging for many people and having to decide to withdraw life sustaining therapies can be extremely difficult. Helping surrogates to refocus their decisions on informed non-dissent can greatly minimize unnecessary suffering for all involved. This case study describes how dignitary harm was minimized by using the concept of informed non-dissent.